Advancing Ecological Understanding and Sustainable Management of Small Pelagic Fish - Myron A. Peck; Ignacio A. Catalán; Ryan R. Rykaczewski; Akinori Takasuka; Susana Garrido; Rebecca G. Asch; Matthew R. Baker; Noelle M. Bowlin; Jennifer Boldt; Richard D. Brodeur; Cecilie Hansen; Salvador E. Lluch‐Cota; et al. (Fish and Fisheries, 2026)
Small pelagic fish (SPF) are critical to the trophodynamic structure and function of marine systems and support some of the most valuable and socially important fisheries worldwide. Their “boom and bust” population dynamics, shifts in distribution, and importance as forage resources for other fish stocks place unique challenges to assessing and managing SPF. In response to these challenges, an international working group was formed in 2019 to foster collaboration aimed at closing key knowledge gaps in the ecology and sustainable management of SPF. Here, that group reviews progress made over the last ~10 years and identifies priorities for the next stage of coordinated international collaboration. Key research needs include: (i) enhancing monitoring programs to capture shifts in SPF distribution and incorporating new technologies, from molecular tools and digital imaging to biophysical and ecological modelling, (ii) improving data sharing to better understand life‐history bottlenecks and cross‐regional population dynamics, (iii) advancing process‐based studies on oceanic and trophodynamic interactions to clarify the ecological roles of SPF as both predators and prey, and (iv) conducting bioeconomic and risk analyses to assess the vulnerability of fishing‐dependent human communities to environmental and fish population fluctuations. A key pathway forward involves integrating mechanistic ecological knowledge, ecosystem and bioeconomic modelling, and social‐ecological frameworks into real‐time, adaptive, and equitable management approaches. This integration will be essential for developing resilient, ecosystem‐based fisheries management capable of anticipating tipping points, accommodating non‐stationary population dynamics, and ensuring sustainability under future climate and socio‐economic uncertainties.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Distributed optical fibre sensing in physical oceanography: emergence and future prospects - Alberto C. Naveira Garabato; Carl P. Spingys; Andrew J. Lucas; Tiago S. Dotto; Christian T. Wild; Scott W. Tyler; Ted A. Scambos; Christopher B. Kratt; Giuseppe Cappelli; Ethan F. Williams; Mariona Claret; Hannah E. Glover; et al. (Ocean Science, 2026)
Distributed optical fibre sensing (DOFS) is a technology that enables continuous, real-time measurements of a range of environmental parameters along the length of a fibre optic cable. In this article, we review the recently emerged applications of DOFS techniques in physical oceanography and offer a perspective on the technology's potential for future growth within the field. The introduction of DOFS to physical oceanography is contextualised with a brief history of the technology, which spun off primarily from the use of seafloor-laid optical fibres for telecommunications purposes. The key components and underpinning physics of a DOFS system are outlined and, on their basis, the suite of variables that are observable with DOFS are discussed. The implementation factors of DOFS, which include trade-offs between measurement accuracy and spatio-temporal resolutions and ranges, are also examined. The physical oceanographic applications of DOFS to date are then illustrated with case examples of four distinct DOFS techniques: distributed temperature sensing (DTS), which can provide ocean temperature observations; distributed static strain sensing (DSS) and distributed acoustic sensing (DAS), which are sensitive to temperature, cable strain and strain-associated variables, such as pressure and ocean velocity; and ultra-long-range observations of ocean currents with optical interferometry. The forthcoming prospects of DOFS in physical oceanography are considered, and are proposed to include new fibre optic-based approaches to sense ocean salinity and measure through the water column. We conclude with reflections on the future role of DOFS within the Global Ocean Observing System, and highlight the opportunities provided by the existing world-wide network of seafloor-laid optical fibres.

Modelling the spread and management of Varroa destructor in naive european honeybee populations - Isobel R. Abell; Thao P. Le; Jennifer A. Flegg; Christopher M. Baker (Journal of Theoretical Biology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Global uncertainty assessment of vegetation indices from NASA's Harmonized Landsat and Sentinel-2 Project - Qiang Zhou; Christopher S.R. Neigh; Junchang Ju; Margaret Wooten; Zhe Zhu; Tomoaki Miura; Petya K.E. Campbell; Madhu K. Sridhar; Bradley W. Baker; Rodrigo V. Leite (Remote Sensing of Environment, 2026)

Minimizing use of nonhuman primates to inform risk to fertility and of adverse pregnancy outcomes with pharmaceuticals - Christopher J. Bowman; Ann Baker; Diann L. Blanset; Kimberly C. Brannen; Gary J. Chellman; Brian Enright; Wendy Halpern; Bethany R. Hannas; Kazushige Maki; Fumito Mikashima; Shermaine Mitchell-Ryan; Eve Mylchreest; et al. (Regulatory Toxicology and Pharmacology, 2026)

The potential impact of forest loss on drinking water treatment costs in the southeastern U.S. - Arpita Nehra; Justin S. Baker; Peter V. Caldwell; Katherine L. Martin; Travis W. Warziniack; Richard H. Manner; Christopher M. Mihiar; Gregory E. Frey; Jennifer K. Costanza (Forest Policy and Economics, 2025)

Whole Genome Sequencing Reveals How Plasticity and Genetic Differentiation Underlie Sympatric Morphs of Arctic Charr - Khrystyna Kurta; Mariano Olivera Fedi; Kendall Baker; Tom Barker; Leah Catchpole; Claudio Ciofi; Arianna Cocco; Joanna Collins; Genevieve Diedericks; Maria Angela Diroma; Alex Durrant; Kjetil Hindar; et al. (Molecular Ecology, 2025)
Salmonids have a remarkable ability to form sympatric morphs after postglacial colonisation of freshwater lakes. These morphs often differ in morphology, feeding and spawning behaviour. Here, we explored the genetic basis of morph differentiation in Arctic charr ( n = 283) by first establishing a high‐quality reference genome and then using this in whole genome sequencing of distinct morphs present in two Norwegian and two Icelandic lakes. The four lakes represent the spectrum of genetic differentiation between morphs from one lake with no genetic differentiation between morphs, implying phenotypic plasticity, to two lakes with locus‐specific genetic differentiation, implying incomplete reproductive isolation, and one lake with strong genome‐wide divergence consistent with complete reproductive isolation. As many as 12 putative inversions ranging from 0.45 to 3.25 Mbp in size segregated among the four morphs present in one lake, Thingvallavatn, and these contributed significantly to the genetic differentiation among morphs. None of the putative inversions were found in any of the other lakes, but there were cases of partial haplotype sharing in similar morph contrasts in other lakes. Our findings are consistent with a highly polygenic basis of morph differentiation with population‐specific selection on alleles linked to the development of similar morph phenotypes. The results support a model where morph differentiation is first established through phenotypic plasticity, leading to niche expansion and separation. This may be followed by gradual development of reproductive isolation, locus‐specific differentiation and eventually complete reproductive isolation and genome‐wide divergence.

Ranking River basins for stream temperature research and monitoring in the contiguous United States - Ramon C. Naranjo; Zachary C. Johnson; Lisa V. Lucas; Nancy T. Baker; Christopher T. Green (Journal of Hydrology, 2025)

Reproductive biology of two hydrothermal vent Cocculinidae species (Mollusca: Gastropoda) from the Arctic and Southern Ocean - Christopher MacNeil; Maria Baker; Jon Copley; Paul Tyler; Ana Hilario; Eva Ramirez-Llodra (Marine Biology, 2025)
The ecology of hydrothermal vents in polar oceans is less known than other regions, as a consequence of the logistical challenges of deep-sea fieldwork at high latitudes, and particularly under permanent ice cover in the Arctic. This paper describes the reproductive biology of the first two cocculinid gastropods sampled from hydrothermal vents: Cocculina enigmadonta from Kemp Caldera, in the Southern Ocean, and Cocculina aurora (Chen et al., Royal Soc Open Sci, https://doi.org/10.1098/rsos.220885 , 2022) from the Aurora Vent Field, Gakkel Ridge, in the Central Arctic Ocean. Histological analysis was used to describe oogenesis, size at first reproduction and fecundity, whilst individual size-frequency distributions from morphometric measurements were produced to investigate demographic population structure. Both species exhibited similar gametogenic patterns with all but three individuals possessing all oocyte developmental stages. Cocculina enigmadonta and C. aurora had similar reproductive strategies, exhibiting low fecundities. For C. enigmadonta the mean fecundity was 16.1 ± 9.3 mature oocytes and for C. aurora 4.1 ± 2.4 mature oocytes. Gametogenic maturity, mean oocyte diameter and instantaneous fecundity were statistically significantly different between species. Overall, both species presented asynchronous reproduction, quasi-continuous gametogenesis and discontinuous recruitment. Importantly, our results provide the first account of the reproductive biology of cocculinid species from hydrothermal vents and discuss their adaptive life-history traits to inhabiting unstable vent environments.

Acclimation conditions and subsequent acute hypoxia challenges do not affect the frequency of erythrocyte nuclear segmentation in triploid brook charr Salvelinus fontinalis ( Mitchill 1814) - John D. Clark; Christopher A. Baker; Sarah A. McGeachy; Rebecca R. Jensen; Tillmann J. Benfey (Journal of Fish Biology, 2025)
Routine observations of blood smears have repeatedly shown that triploid fish have a greater proportion of erythrocytes with nuclear segmentation (ENS) than diploids; however, there is as yet no understanding of why this is the case and whether it affects erythrocyte function. In an attempt to address this, we examined blood smears from two previous experiments to determine whether ENS frequency is affected by rearing conditions (acclimation temperature or dissolved oxygen level) and subsequent acute aerobic distress in diploid and triploid brook charr Salvelinus fontinalis (Mitchill 1814). As expected, triploids had a higher ENS frequency than corresponding diploids, but with no biologically significant effect of experimental conditions on ENS frequency in triploids. ENS was too rare to examine the effects of these conditions in diploids.

Scanners, satellites, smart compactors, and drones: Emerging technologies for assessing compacted soil lift thickness - Christopher L. Meehan; William J. Baker III (Transportation Geotechnics, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Opportunities for Earth Observation to Inform Risk Management for Ocean Tipping Points - Richard A. Wood; Jonathan A. Baker; Grégory Beaugrand; Jacqueline Boutin; Alessandra Conversi; Reik V. Donner; Ivy Frenger; Eric Goberville; Hakase Hayashida; Wolfgang Koeve; Karin Kvale; Angela Landolfi; et al. (Surveys in Geophysics, 2025)
As climate change continues, the likelihood of passing critical thresholds or tipping points increases. Hence, there is a need to advance the science for detecting such thresholds. In this paper, we assess the needs and opportunities for Earth Observation (EO, here understood to refer to satellite observations) to inform society in responding to the risks associated with ten potential large-scale ocean tipping elements: Atlantic Meridional Overturning Circulation; Atlantic Subpolar Gyre; Beaufort Gyre; Arctic halocline; Kuroshio Large Meander; deoxygenation; phytoplankton; zooplankton; higher level ecosystems (including fisheries); and marine biodiversity. We review current scientific understanding and identify specific EO and related modelling needs for each of these tipping elements. We draw out some generic points that apply across several of the elements. These common points include the importance of maintaining long-term, consistent time series; the need to combine EO data consistently with in situ data types (including subsurface), for example through data assimilation; and the need to reduce or work with current mismatches in resolution (in both directions) between climate models and EO datasets. Our analysis shows that developing EO, modelling and prediction systems together, with understanding of the strengths and limitations of each, provides many promising paths towards monitoring and early warning systems for tipping, and towards the development of the next generation of climate models.

The AGN-201 Digital Twin: A test bed for remotely monitoring nuclear reactors - Ryan Stewart; Eduardo Treviño; Ashley Shields; Kolton Heaps; John Darrington; Quinton Williams; Chad Pope; Johnathan Scott; Benjamin Baker; Jaden Palmer; Benoni Vainqueur; Todd S. Palmer; et al. (Annals of Nuclear Energy, 2025)

Changing climate and disturbance effects on southwestern US forests - Matthew D. Hurteau; Reese Baker; Kyle Gonterman; Abigail Granath; Josh Lopez-Binder; M. Dylan Taylor; Lorraina S. Rojas; Lindsey Rotche; Andy Graves; Marissa J. Goodwin; Gavin Jones; Christopher Marsh (Forest Ecology and Management, 2025)

Prioritizing US Geological Survey science on salinization and salinity in candidate and selected priority river basins - Christopher H. Conaway; Nancy T. Baker; Craig J. Brown; Christopher T. Green; Douglas B. Kent (Environmental Monitoring and Assessment, 2024)
The US Geological Survey (USGS) is selecting and prioritizing basins, known as Integrated Water Science basins, for monitoring and intensive study. Previous efforts to aid in this selection process include a scientifically defensible and quantitative assessment of basins facing human-caused water resource challenges (Van Metre et al. in Environmental Monitoring and Assessment , 192 (7), 458 2020). In the present work, we explore this ranking process based on water quality considerations, specifically salinity and salinization. We selected top candidate basins to study salinity and salinization issues in 18 hydrologic regions that include 163 candidate basins. Our prioritization is based on quantitative assessment of sources of salinity, drivers of change, and receptors that must respond to those sources and drivers. Source terms represented in the prioritization include geology, depth to brackish groundwater, stream conductivity, chloride in precipitation, urban and agricultural land use, application of road salt as a deicer, and irrigation. Drivers represented in prioritization include changes in chemical weathering as a result of changes in rainwater chemistry. Receptors include measures of water stress, measurements of stream ecological health, and socioeconomic factors. In addition, we present research activities for the USGS on salinity and salinization that can be pursued in these basins including assessment of sources, pathways, and loadings; predicting and understanding changes in sources, peaks, and trends; understanding the components of salinity and mobilization of contaminants; understanding the relationship between salinization and changing ecosystems; and developing knowledge on the causes and distribution of groundwater salinity, brackish water resources, and challenges related to desalination.

Fire-induced shifts in stalagmite organic matter mapped using Synchrotron infrared microspectroscopy - Liza K. McDonough; Micheline Campbell; Pauline C. Treble; Christopher Marjo; Silvia Frisia; Jitraporn Vongsvivut; Annaleise R. Klein; Viktoria Kovacs-Kis; Andy Baker (Organic Geochemistry, 2024)

Minimally Invasive Intracerebral Hemorrhage Evacuation Improves Pericavity Cerebral Blood Volume - Colton J. Smith; Christina P. Rossitto; Michael Manhart; Imke Fuhrmann; Julie DiNitto; Turner Baker; Muhammad Ali; Marily Sarmiento; J Mocco; Christopher P. Kellner (Translational Stroke Research, 2024)

Olfactory tract/bulb metal concentration in Manganese-exposed mineworkers - Luis F. Gonzalez-Cuyar; Gill Nelson; Susan Searles Nielsen; Wendy W. Dlamini; Amelia Keyser-Gibson; C. Dirk Keene; Michael Paulsen; Susan R. Criswell; Natalie Senini; Lianne Sheppard; Shar Samy; Christopher D. Simpson; et al. (NeuroToxicology, 2024)

Lunar Flashlight science ground and flight measurements and operations using a multi-band laser reflectometer - Barbara A. Cohen; Ryan R. Petersburg; Daniel R. Cremons; Patrick S. Russell; Paul O. Hayne; Benjamin T. Greenhagen; David A. Paige; Jose Martinez Camacho; Nathan Cheek; Mark T. Sullivan; Valeria Lopez Robles; Jessica Ban; et al. (Icarus, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Sources of variation in nutrient loads collected through street sweeping in the Minneapolis-St. Paul Metropolitan Area, Minnesota, USA - Sarah E. Hobbie; Rachel A. King; Tessa Belo; Paula Kalinosky; Lawrence A. Baker; Jacques C. Finlay; Christopher A. Buyarski; Ross Bintner (Science of The Total Environment, 2023)

Anthropometric measures and arsenic methylation among pregnant women in rural northern Bangladesh - Tyler J.S. Smith; Ana Navas-Acien; Sarah Baker; Caryn Kok; Kate Kruczynski; Lindsay N. Avolio; Nora Pisanic; Pranay R. Randad; Rebecca C. Fry; Walter Goessler; Alexander van Geen; Jessie P. Buckley; et al. (Environmental Research, 2023)

Forested watersheds provide the highest water quality among all land cover types, but the benefit of this ecosystem service depends on landscape context - Peter V. Caldwell; Katherine L. Martin; James M. Vose; Justin S. Baker; Travis W. Warziniack; Jennifer K. Costanza; Gregory E. Frey; Arpita Nehra; Christopher M. Mihiar (Science of The Total Environment, 2023)

Risk assessments for the dietary intake aflatoxins in food: A systematic review (2016–2022) - Kiran Bhardwaj; Julie P. Meneely; Simon A. Haughey; Moira Dean; Patrick Wall; Guangtao Zhang; Bob Baker; Christopher T. Elliott (Food Control, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Surface Inactivation of a SARS-CoV-2 Surrogate with Hypochlorous Acid is Impacted by Surface Type, Contact Time, Inoculum Matrix, and Concentration - Allyson N. Hamilton; Sahaana Chandran; Christopher A. Baker; Kristen E. Gibson (Food and Environmental Virology, 2023)

The phylogeny and global biogeography of Primulaceae based on high-throughput DNA sequence data - Drew A. Larson; Andre S. Chanderbali; Olivier Maurin; Deise J.P. Gonçalves; Christopher W. Dick; Douglas E. Soltis; Pamela S. Soltis; Peter W. Fritsch; James J. Clarkson; Aurélie Grall; Nina M.J. Davies; Isabel Larridon; et al. (Molecular Phylogenetics and Evolution, 2023)

Transfer learning in a biomaterial fibrosis model identifies in vivo senescence heterogeneity and contributions to vascularization and matrix production across species and diverse pathologies - Christopher Cherry; James I. Andorko; Kavita Krishnan; Joscelyn C. Mejías; Helen Hieu Nguyen; Katlin B. Stivers; Elise F. Gray-Gaillard; Anna Ruta; Jin Han; Naomi Hamada; Masakazu Hamada; Ines Sturmlechner; et al. (GeroScience, 2023)

Designing an expert-led Bayesian network to understand interactions between policy instruments for adoption of eco-friendly farming practices - Helen J. Mayfield; Rachel Eberhard; Christopher Baker; Umberto Baresi; Michael Bode; Anthea Coggan; Angela J. Dean; Felicity Deane; Evan Hamman; Diane Jarvis; Barton Loechel; Bruce M. Taylor; et al. (Environmental Science & Policy, 2023)

Hot Vents Beneath an Icy Ocean: The Aurora Vent Field, Gakkel Ridge, Revealed - Eva Ramirez-Llodra; Claudio Argentino; Maria Baker; Antje Boetius; Carolina Costa; Håkon Dahle; Emily Denny; Pierre-Antoine Dessandier; Mari Eilertsen; Benedicte Ferre; Christopher German; Kevin Hand; et al. (Oceanography, 2023)
Evidence of hydrothermal venting on the ultra-slow spreading Gakkel Ridge in the Central Arctic Ocean has been available since 2001, with first visual evidence of black smokers on the Aurora Vent Field obtained in 2014. But it was not until 2021 that the first ever remotely operated vehicle (ROV) dives to hydrothermal vents under permanent ice cover in the Arctic were conducted, enabling the collection of vent fluids, rocks, microbes, and fauna. In this paper, we present the methods employed for deep-sea ROV operations under drifting ice. We also provide the first description of the Aurora Vent Field, which includes three actively venting black smokers and diffuse flow on the Aurora mound at ~3,888 m depth on the southern part of the Gakkel Ridge (82.5°N). The biological communities are dominated by a new species of cocculinid limpet, two small gastropods, and a melitid amphipod. The ongoing analyses of Aurora Vent Field samples will contribute to positioning the Gakkel Ridge hydrothermal vents in the global biogeographic puzzle of hydrothermal vents.

Projecting U.S. forest management, market, and carbon sequestration responses to a high-impact climate scenario - Justin S. Baker; George Van Houtven; Jennifer Phelan; Gregory Latta; Christopher M. Clark; Kemen G. Austin; Olakunle E. Sodiya; Sara B. Ohrel; John Buckley; Lauren E. Gentile; Jeremy Martinich (Forest Policy and Economics, 2023)

Stand Inventories as an Early Detection System for Forest Health Threats - Paul A Klockow; Christopher B Edgar; Marcella A Windmuller-Campione; Fred A Baker (Forest Science, 2023)
Pest-specific inventories require substantial resources and are often infeasible, creating a need for alternative means of early pest detection. We examined the potential for stand inventories to detect forest health threats by using a unique dataset of mapped eastern spruce dwarf mistletoe (Arceuthobium pusillum Peck.) infestations in black spruce (Picea mariana Mill. B.S.P) stands of northern Minnesota, USA. We simulated stand inventories across a range of sampling intensities; that is, current standard (S) methods in Minnesota, adding one plot (S + 1), doubling the intensity (2S), and halving the intensity (S/2), using fixed-radius plots and transect buffers for detection. We categorized stands into low, moderate, and high infestation severity. We simulated detection at multiple viewing distances along S inventory transects in low severity infestation stands. Detection probability increased as sampling intensity increased. Plot-based detection averaged > 50% for moderate and high severity infestations except S/2 in moderate severity infestations. Notably, transect-based detection averaged ≥ 85% at viewing distances of 25 to 100 m. Results suggest stand inventories could provide opportunities to detect forest health threats with unique signatures when transect observations are included. Thus, forest health specialists may consider including pest-specific training for foresters in current inventory methods, requiring modest investment of time and effort.

Contributions of healthier diets and agricultural productivity toward sustainability and climate goals in the United States - Grace C. Wu; Justin S. Baker; Christopher M. Wade; Gordon C. McCord; Joseph E. Fargione; Petr Havlik (Sustainability Science, 2023)
Meeting ambitious climate targets will require deploying the full suite of mitigation options, including those that indirectly reduce greenhouse-gas (GHG) emissions. Healthy diets have sustainability co-benefits by directly reducing livestock emissions as well as indirectly reducing land use emissions. Increased crop productivity could indirectly avoid emissions by reducing cropland area. However, there is disagreement on the sustainability of proposed healthy U.S. diets and a lack of clarity on how long-term sustainability benefits may change in response to shifts in the livestock sector. Here, we explore the GHG emissions impacts of seven scenarios that vary U.S. crop yields and healthier diets in the U.S. and overseas. We also examine how impacts vary across assumptions of future ruminant livestock productivity and ruminant stocking density in the U.S. We employ two complementary land use models—the US FABLE Calculator, an agricultural and forestry sector accounting model with high agricultural commodity representation, and GLOBIOM, a spatially explicit partial equilibrium optimization model for global land use systems. Results suggest that healthier U.S. diets that follow the Dietary Guidelines for Americans reduce agricultural and land use greenhouse gas emissions by 25–57% (approx 120–310 MtCO 2e /y) and pastureland area by 28–38%. The potential emissions and land sparing benefits of U.S. agricultural productivity growth are modest within the U.S. due to the increasing comparative advantage of U.S. crops. Our findings suggest that healthy U.S. diets can significantly contribute toward meeting U.S. long-term climate goals for the land use sectors.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Tebufenozide has limited direct effects on simulated aquatic communities - Christopher Edge; Leanne Baker; Emily Smenderovac; Shane Heartz; Erik Emilson (Ecotoxicology, 2022)
The use of insecticides to control undesirable pest species in forestry has undergone a shift from broad spectrum to narrow spectrum insecticides to reduce the risk of effects on non-target species. However, there is still risk of direct effects on non-target species as some insecticides function as hormone mimics, or through indirect pathways as the insecticide is broken down in the environment. Tebufenozide, an ecdysone hormone mimic, is the active ingredient in insecticides used in a variety of large scale pest control programs. An oft cited reason for the safety of Tebufenozide is that it is rapidly broken down in the environment by microbes. We investigated the potential non-target effects of two Tebufenozide formulations used in Canada, Mimic 240LV and Limit 240, on aquatic communities using an outdoor mesocosm experiment. We focus on direct effects on amphibian larvae (wood frog, Rana sylvaticus ), zooplankton communities, and effects on biofilm and phytoplanktonic microbial communities that could arise from either direct toxicity, or from breaking down the insecticide as a nutrient and/or carbon source. There was limited evidence for direct effects on amphibian larvae or zooplankton communities. There were small but non-significant shifts in biofilm microbial communities responsible for nutrient cycling. Beta diversity in the plankton community was slightly higher among tanks treated with insecticide indicating a community dispersion/disbiosis effect. Overall, we found limited evidence of negative effects, however, subtle changes to microbial communities did occur and could indicate changes to ecosystem function.

Modeling total predation to avoid perverse outcomes from cat control in a data‐poor island ecosystem - Michaela Plein; Katherine R. O'Brien; Matthew H. Holden; Matthew P. Adams; Christopher M. Baker; Nigel G. Bean; Scott A. Sisson; Michael Bode; Kerrie L. Mengersen; Eve McDonald‐Madden (Conservation Biology, 2022)
Data‐hungry, complex ecosystem models are often used to predict the consequences of threatened species management, including perverse outcomes. Unfortunately, this approach is impractical in the many systems that have insufficient data to parameterize ecosystem interactions or reliably calibrate or validate such models. We devised a different approach composed of a minimum realistic model that guides decisions in data‐ and resource‐scarce systems. We applied our approach to a case study in an invaded ecosystem from Christmas Island, Australia, where there are concerns that cat ( Felis catus ) eradication to protect native species, including the red‐tailed tropicbird ( Phaethon rubricauda ), could release mesopredation by invasive rats ( Rattus rattus ). We used biophysical constraints (metabolic demand) and observable parameters (e.g., prey preferences) to identify the combined cat and rat abundances that could threaten the tropicbird population. The population of tropicbirds was not sustained when predated by 1607 rats (95% credible interval [CI]: 103–5910) in the absence of cats and 21 cats (95% CI: 2–82) in the absence of rats. For every cat removed from the island, the bird's net population growth rate improved, provided rats did not increase by more than 77 individuals (95% CI: 30–174). Thus, in this context, 1 cat is equivalent to 30–174 rats. Our methods are especially useful for on‐the‐ground predator control in the absence of knowledge of predator–predator interactions to determine whether current abundance of predators threatened the prey population of interest; managing only 1 predator species was sufficient to protect the prey species given potential release of another predator; and control of multiple predator species was needed to meet the conservation goal. With our approach limited information can be used for maximum value in data‐poor systems because it shifts the focus from predicting future trajectories to identifying conditions that impede conservation.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

One object, two networks? Assessing the relationship between the face and body-selective regions in the primate visual system - Jessica Taubert; J. Brendan Ritchie; Leslie G. Ungerleider; Christopher I. Baker (Brain Structure and Function, 2022)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

The PshX subunit of the photochemical reaction center from Heliobacterium modesticaldum acts as a low-energy antenna - Gregory S. Orf; Christopher J. Gisriel; Jesse Granstrom; Patricia L. Baker; Kevin E. Redding (Photosynthesis Research, 2022)

Dynamical mechanisms linking Indian monsoon precipitation and the circumglobal teleconnection - Jonathan D. Beverley; Steven J. Woolnough; Laura H. Baker; Stephanie J. Johnson; Antje Weisheimer; Christopher H. O’Reilly (Climate Dynamics, 2021)
The circumglobal teleconnection (CGT) is an important mode of circulation variability, with an influence across many parts of the northern hemisphere. Here, we examine the excitation mechanisms of the CGT in the ECMWF seasonal forecast model, and the relationship between the Indian summer monsoon (ISM), the CGT and the extratropical northern hemisphere circulation. Results from relaxation experiments, in which the model is corrected to reanalysis in specific regions, suggest that errors over northwest Europe are more important in inhibiting the model skill at representing the CGT, in addition to northern hemisphere skill more widely, than west-central Asia and the ISM region, although the link between ISM precipitation and the extratropical circulation is weak in all experiments. Thermal forcing experiments in the ECMWF model, in which a heating is applied over India, suggest that the ISM does force an extratropical Rossby wave train, with upper tropospheric anticyclonic anomalies over east Asia, the North Pacific and North America associated with increased ISM heating. However, this eastward-propagating branch of the wave train does not project into Europe, and the response there occurs largely through westward-propagating Rossby waves. Results from barotropic model experiments show a response that is highly consistent with the seasonal forecast model, with similar eastward- and westward-propagating Rossby waves. This westward-propagating response is shown to be important in the downstream reinforcement of the wave train between Asia and North America.

Human Actions Alter Tidal Marsh Seascapes and the Provision of Ecosystem Services - Ben L. Gilby; Michael P. Weinstein; Ronald Baker; Just Cebrian; Scott B. Alford; Ariella Chelsky; Denise Colombano; Rod M. Connolly; Carolyn A. Currin; Ilka C. Feller; Alyssa Frank; Janelle A. Goeke; et al. (Estuaries and Coasts, 2021)

Resource availability and heterogeneity shape the self‐organisation of regular spatial patterning - Jessica A. Castillo Vardaro; Juan A. Bonachela; Christopher C. M. Baker; Malin L. Pinsky; Daniel F. Doak; Robert M. Pringle; Corina E. Tarnita (Ecology Letters, 2021)
Explaining large‐scale ordered patterns and their effects on ecosystem functioning is a fundamental and controversial challenge in ecology. Here, we coupled empirical and theoretical approaches to explore how competition and spatial heterogeneity govern the regularity of colony dispersion in fungus‐farming termites. Individuals from different colonies fought fiercely, and inter‐nest distances were greater when nests were large and resources scarce—as expected if competition is strong, large colonies require more resources and foraging area scales with resource availability. Building these principles into a model of inter‐colony competition showed that highly ordered patterns emerged under high resource availability and low resource heterogeneity. Analysis of this dynamical model provided novel insights into the mechanisms that modulate pattern regularity and the emergent effects of these patterns on system‐wide productivity. Our results show how environmental context shapes pattern formation by social‐insect ecosystem engineers, which offers one explanation for the marked variability observed across ecosystems.

Spatiotemporal patterns of ENSO‐precipitation relationships in the tropical Andes of southern Peru and Bolivia - Joseph A. Jonaitis; L. Baker Perry; Peter T. Soulé; Christopher Thaxton; Marcos F. Andrade‐Flores; Tania Ita Vargas; Laura Ticona (International Journal of Climatology, 2021)
Precipitation in the outer tropical Andes is highly seasonal, exhibits considerable interannual variability, and is vital for regulating freshwater availability, flooding, glacier mass balance, and droughts. The primary driver of interannual variability is El Niño Southern Oscillation (ENSO), with most investigations reporting that the El Niño (La Niña) results in negative (positive) precipitation anomalies across the region. Recent investigations, however, have identified substantial spatiotemporal differences in ENSO‐precipitation relationships. Motivated by the dissimilarity of these findings, this study examines a carefully selected data set (≥ 90% completeness) of ground‐based precipitation observations from 75 high‐elevation (≥ 2,500 m above sea level) meteorological stations in the tropical Andes of southern Peru and Bolivia for the period 1972–2016. Distinct groups of stations and associated variability in precipitation characteristics (e.g., total seasonal precipitation, wet season onset, and wet season length) are identified. Using no spatial constraints, the K‐Means algorithm optimally grouped stations into five easily identifiable groups. The groups farthest from the Amazon basin had significant negative (positive) precipitation anomalies ( p

Observing Life in the Sea Using Environmental DNA - Francisco Chavez; Markus Min; Kathleen Pitz; Nathan Truelove; Jacoby Baker; Diana LaScala-Grunewald; Marguerite Blum; Kristine Walz; Charles Nye; Anni Djurhuus; Robert Miller; Kelly Goodwin; et al. (Oceanography, 2021)
The use of environmental DNA (eDNA) for studying the ecology and variability of life in the sea is reviewed here in the context of US interagency Marine Biodiversity Observation Network (MBON) projects. Much of the information in this paper comes from samples collected within US National Marine Sanctuaries. The field of eDNA is relatively new but growing rapidly, and it has the potential to disrupt current paradigms developed on the basis of existing measurement methods. After a general review of the field, we provide specific examples of the type of information that eDNA provides regarding the changing distribution of life in the sea over space (horizontally and vertically) and time. We conclude that eDNA analyses yield results that are similar to those collected using traditional observation methods, are complementary to them, and because of the breadth of information provided, have the potential to improve conservation and management practices. Moreover, through technology development and standardization of methods, eDNA offers a means to scale biological observations globally to a level similar to those currently made for ocean physics and biogeochemistry. This scaling can ultimately result in a far better understanding of global marine biodiversity and contribute to better management and sustainable use of the world ocean. Improved information management systems that track methods and associated metadata, together with international coordination, will be needed to realize a global eDNA observation network.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Spatial patterning of soil microbial communities created by fungus‐farming termites - Christopher C. M. Baker; Jessica A. Castillo Vardaro; Daniel F. Doak; Johan Pansu; Jérémy Puissant; Robert M. Pringle; Corina E. Tarnita (Molecular Ecology, 2020)
Spatially overdispersed mounds of fungus‐farming termites (Macrotermitinae) are hotspots of nutrient availability and primary productivity in tropical savannas, creating spatial heterogeneity in communities and ecosystem functions. These termites influence the local availability of nutrients in part by redistributing nutrients across the landscape, but the links between termite ecosystem engineering and the soil microbes that are the metabolic agents of nutrient cycling are little understood. We used DNA metabarcoding of soils from Odontotermes montanus mounds to examine the influence of termites on soil microbial communities in a semi‐arid Kenyan savanna. We found that bacterial and fungal communities were compositionally distinct in termite‐mound topsoils relative to the surrounding savanna, and that bacterial communities were more diverse on mounds. The higher microbial alpha and beta diversity associated with mounds created striking spatial patterning in microbial community composition, and boosted landscape‐scale microbial richness and diversity. Selected enzyme assays revealed consistent differences in potential enzymatic activity, suggesting links between termite‐induced heterogeneity in microbial community composition and the spatial distribution of ecosystem functions. We conducted a large‐scale field experiment in which we attempted to simulate termites’ effects on microbes by fertilizing mound‐sized patches; this altered both bacterial and fungal communities, but in a different way than natural mounds. Elevated levels of inorganic nitrogen, phosphorus and potassium may help to explain the distinctive fungal communities in termite‐mound soils, but cannot account for the distinctive bacterial communities associated with mounds.

Genomic islands of divergence infer a phenotypic landscape in Pacific lamprey - Jon E. Hess; Jeramiah J. Smith; Nataliya Timoshevskaya; Cyndi Baker; Christopher C. Caudill; David Graves; Matthew L. Keefer; Andrew P. Kinziger; Mary L. Moser; Laurie L. Porter; Greg Silver; Steven L. Whitlock; et al. (Molecular Ecology, 2020)
High rates of dispersal can breakdown coadapted gene complexes. However, concentrated genomic architecture (i.e., genomic islands of divergence) can suppress recombination to allow evolution of local adaptations despite high gene flow. Pacific lamprey ( Entosphenus tridentatus ) is a highly dispersive anadromous fish. Observed trait diversity and evidence for genetic basis of traits suggests it may be locally adapted. We addressed whether concentrated genomic architecture could influence local adaptation for Pacific lamprey. Using two new whole genome assemblies and genotypes from 7,716 single nucleotide polymorphism (SNP) loci in 518 individuals from across the species range, we identified four genomic islands of divergence (on chromosomes 01, 02, 04, and 22). We determined robust phenotype‐by‐genotype relationships by testing multiple traits across geographic sites. These trait associations probably explain genomic divergence across the species’ range. We genotyped a subset of 302 broadly distributed SNPs in 2,145 individuals for association testing for adult body size, sexual maturity, migration distance and timing, adult swimming ability, and larval growth. Body size traits were strongly associated with SNPs on chromosomes 02 and 04. Moderate associations also implicated SNPs on chromosome 01 as being associated with variation in female maturity. Finally, we used candidate SNPs to extrapolate a heterogeneous spatiotemporal distribution of these predicted phenotypes based on independent data sets of larval and adult collections. These maturity and body size results guide future elucidation of factors driving regional optimization of these traits for fitness. Pacific lamprey is culturally important and imperiled. This research addresses biological uncertainties that challenge restoration efforts.

Stimulation of isoprene emissions and electron transport rates as key mechanisms of thermal tolerance in the tropical species Vismia guianensis - Tayana B. Rodrigues; Christopher R. Baker; Anthony P. Walker; Nate McDowell; Alistair Rogers; Niro Higuchi; Jeffrey Q. Chambers; Kolby J. Jardine (Global Change Biology, 2020)
Tropical forests absorb large amounts of atmospheric CO 2 through photosynthesis, but high surface temperatures suppress this absorption while promoting isoprene emissions. While mechanistic isoprene emission models predict a tight coupling to photosynthetic electron transport (ETR) as a function of temperature, direct field observations of this phenomenon are lacking in the tropics and are necessary to assess the impact of a warming climate on global isoprene emissions. Here we demonstrate that in the early successional species Vismia guianensis in the central Amazon, ETR rates increased with temperature in concert with isoprene emissions, even as stomatal conductance ( g s ) and net photosynthetic carbon fixation ( P n ) declined. We observed the highest temperatures of continually increasing isoprene emissions yet reported (50°C). While P n showed an optimum value of 32.6 ± 0.4°C, isoprene emissions, ETR, and the oxidation state of PSII reaction centers (q L ) increased with leaf temperature with strong linear correlations for ETR (ƿ = 0.98) and q L (ƿ = 0.99) with leaf isoprene emissions. In contrast, other photoprotective mechanisms, such as non‐photochemical quenching, were not activated at elevated temperatures. Inhibition of isoprenoid biosynthesis repressed P n at high temperatures through a mechanism that was independent of stomatal closure. While extreme warming will decrease g s and P n in tropical species, our observations support a thermal tolerance mechanism where the maintenance of high photosynthetic capacity under extreme warming is assisted by the simultaneous stimulation of ETR and metabolic pathways that consume the direct products of ETR including photorespiration and the biosynthesis of thermoprotective isoprenoids. Our results confirm that models which link isoprene emissions to the rate of ETR hold true in tropical species and provide necessary “ground‐truthing” for simulations of the large predicted increases in tropical isoprene emissions with climate warming.

Informing management decisions for ecological networks, using dynamic models calibrated to noisy time‐series data - Matthew P. Adams; Scott A. Sisson; Kate J. Helmstedt; Christopher M. Baker; Matthew H. Holden; Michaela Plein; Jacinta Holloway; Kerrie L. Mengersen; Eve McDonald‐Madden (Ecology Letters, 2020)
Well‐intentioned environmental management can backfire, causing unforeseen damage. To avoid this, managers and ecologists seek accurate predictions of the ecosystem‐wide impacts of interventions, given small and imprecise datasets, which is an incredibly difficult task. We generated and analysed thousands of ecosystem population time series to investigate whether fitted models can aid decision‐makers to select interventions. Using these time‐series data (sparse and noisy datasets drawn from deterministic Lotka‐Volterra systems with two to nine species, of known network structure), dynamic model forecasts of whether a species’ future population will be positively or negatively affected by rapid eradication of another species were correct > 70% of the time. Although 70% correct classifications is only slightly better than an uninformative prediction (50%), this classification accuracy can be feasibly improved by increasing monitoring accuracy and frequency. Our findings suggest that models may not need to produce well‐constrained predictions before they can inform decisions that improve environmental outcomes.

Evaluation of environmental DNA to detect Sistrurus catenatus and Ophidiomyces ophiodiicola in crayfish burrows - Sarah J. Baker; Matthew L. Niemiller; Andrew J. Stites; Kurt T. Ash; Mark. A. Davis; Michael J. Dreslik; Christopher A. Phillips (Conservation Genetics Resources, 2020)

Simultaneous invasive alien predator eradication delivers the best outcomes for protected island species - Christopher M. Baker; Michaela Plein; Rabith Shaikh; Michael Bode (Biological Invasions, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Model of trawlable area using benthic terrain and oceanographic variables—Informing survey design and habitat maps in the Gulf of Alaska - Matthew R. Baker; Wayne Palsson; Mark Zimmermann; Christopher N. Rooper (Fisheries Oceanography, 2019)
Bottom trawl surveys provide fishery‐independent data on relative abundance and life history parameters for a wide range of marine taxa. Survey data are used to assess species distribution, biological interactions, and ecosystem structure and to manage marine resources. Not all bottom types or oceanographic conditions accommodate this survey method. We applied National Ocean Service hydrographic smooth sheets to evaluate physical attributes associated with habitat available to surveys. Random forests were used to evaluate the relative influence of benthic terrain and oceanographic predictors in determining accessibility to bottom trawl gear. We examined the marginal importance of each predictor, quantified the response gradient, and applied piecewise regression to determine threshold breakpoint values. Thresholds were used to develop predictive maps and distinguish untrawlable habitat at the scale of discrete towpaths and survey stations. Untrawlable habitat was associated with increased complexity in terrain, roughness, slope, surface curvature, substrate coarseness, current, and aspect. Maps of critical thresholds suggest different variables constrain the probability of a successful trawl in the nearshore, shelf, and continental slope. Overlay analysis of the model projection demonstrates the utility of archived smooth sheet data and identifies areas where higher resolution data might improve results. The model and maps produced in this analysis might be used to identify habitats available to and impacted by commercial trawl fisheries, inform the relative availability of various species and habitat types to bottom trawl surveys, evaluate bias in assessment indices and ecosystem metrics derived from survey data, and advance habitat‐specific biomass estimates.

Projecting the Spatial Distribution of Possible Planted Forest Expansion in the United States - Christopher M Wade; Justin S Baker; Gregory Latta; Sara B Ohrel; Justine Allpress (Journal of Forestry, 2019)
As the demand for forest products and carbon storage in standing timbers increases, intensive planting of forest resources is expected to increase. With the increased use of plantation practices, it is important to understand the influence that forest plot characteristics have on the likelihood of where these practices are occurring. Depending on the goals of a policy or program, increasing forest planting could be a desirable outcome or something to avoid. This study estimates a spatially explicit logistical regression function to assess the likelihood that forest plots will be planted based on physical, climate, and economic factors. The empirical results are used to project the potential spatial distribution of forest planting, at the intensive and extensive land-use margins, across illustrative future scenarios. Results from this analysis offer insight into the factors that have driven forest planting in the United States historically and the potential distribution of new forest planting in the coming decades under policy or market scenarios that incentivize improved forest productivity or certain ecosystem services provided by intensively managed systems (e.g., carbon sequestration).

Forced summer stationary waves: the opposing effects of direct radiative forcing and sea surface warming - Hugh S. Baker; Tim Woollings; Cheikh Mbengue; Myles R. Allen; Christopher H. O’Reilly; Hideo Shiogama; Sarah Sparrow (Climate Dynamics, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Dominant tree species drive beta diversity patterns in western Amazonia - Frederick C. Draper; Gregory P. Asner; Eurídice N. Honorio Coronado; Timothy R. Baker; Roosevelt García‐Villacorta; Nigel C. A. Pitman; Paul V. A. Fine; Oliver L. Phillips; Ricardo Zárate Gómez; Carlos A. Amasifuén Guerra; Manuel Flores Arévalo; Rodolfo Vásquez Martínez; et al. (Ecology, 2019)
The forests of western Amazonia are among the most diverse tree communities on Earth, yet this exceptional diversity is distributed highly unevenly within and among communities. In particular, a small number of dominant species account for the majority of individuals, whereas the large majority of species are locally and regionally extremely scarce. By definition, dominant species contribute little to local species richness (alpha diversity), yet the importance of dominant species in structuring patterns of spatial floristic turnover (beta diversity) has not been investigated. Here, using a network of 207 forest inventory plots, we explore the role of dominant species in determining regional patterns of beta diversity (community‐level floristic turnover and distance‐decay relationships) across a range of habitat types in northern lowland Peru. Of the 2,031 recorded species in our data set, only 99 of them accounted for 50% of individuals. Using these 99 species, it was possible to reconstruct the overall features of regional beta diversity patterns, including the location and dispersion of habitat types in multivariate space, and distance‐decay relationships. In fact, our analysis demonstrated that regional patterns of beta diversity were better maintained by the 99 dominant species than by the 1,932 others, whether quantified using species‐abundance data or species presence–absence data. Our results reveal that dominant species are normally common only in a single forest type. Therefore, dominant species play a key role in structuring western Amazonian tree communities, which in turn has important implications, both practically for designing effective protected areas, and more generally for understanding the determinants of beta diversity patterns.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Dichomitus squalens partially tailors its molecular responses to the composition of solid wood - Paul Daly; Sara Casado López; Mao Peng; Christopher S. Lancefield; Samuel O. Purvine; Young‐Mo Kim; Erika M. Zink; Alice Dohnalkova; Vasanth R. Singan; Anna Lipzen; David Dilworth; Mei Wang; et al. (Environmental Microbiology, 2018)
Summary White‐rot fungi, such as Dichomitus squalens , degrade all wood components and inhabit mixed‐wood forests containing both soft‐ and hardwood species. In this study, we evaluated how D. squalens responded to the compositional differences in softwood [guaiacyl (G) lignin and higher mannan content] and hardwood [syringyl/guaiacyl (S/G) lignin and higher xylan content] using semi‐natural solid cultures. Spruce (softwood) and birch (hardwood) sticks were degraded by D. squalens as measured by oxidation of the lignins using 2D‐NMR. The fungal response as measured by transcriptomics, proteomics and enzyme activities showed a partial tailoring to wood composition. Mannanolytic transcripts and proteins were more abundant in spruce cultures, while a proportionally higher xylanolytic activity was detected in birch cultures. Both wood types induced manganese peroxidases to a much higher level than laccases, but higher transcript and protein levels of the manganese peroxidases were observed on the G‐lignin rich spruce. Overall, the molecular responses demonstrated a stronger adaptation to the spruce rather than birch composition, possibly because D. squalens is mainly found degrading softwoods in nature, which supports the ability of the solid wood cultures to reflect the natural environment.

Articles You May Have Missed - Nicklaus P. Brandehoff; K. A. Baker; C. F. Bonney; P. C. Ng; J. Schimmel; Christopher O. Hoyte (Journal of Medical Toxicology, 2018)

Human-relevant potency threshold (HRPT) for ERα agonism - Christopher J. Borgert; John C. Matthews; Stephen P. Baker (Archives of Toxicology, 2018)

Monitoring, imperfect detection, and risk optimization of a Tasmanian devil insurance population - Tracy M. Rout; Christopher M. Baker; Stewart Huxtable; Brendan A. Wintle (Conservation Biology, 2018)
Most species are imperfectly detected during biological surveys, which creates uncertainty around their abundance or presence at a given location. Decision makers managing threatened or pest species are regularly faced with this uncertainty. Wildlife diseases can drive species to extinction; thus, managing species with disease is an important part of conservation. Devil facial tumor disease (DFTD) is one such disease that led to the listing of the Tasmanian devil ( Sarcophilus harrisii ) as endangered. Managers aim to maintain devils in the wild by establishing disease‐free insurance populations at isolated sites. Often a resident DFTD‐affected population must first be removed. In a successful collaboration between decision scientists and wildlife managers, we used an accessible population model to inform monitoring decisions and facilitate the establishment of an insurance population of devils on Forestier Peninsula. We used a Bayesian catch‐effort model to estimate population size of a diseased population from removal and camera trap data. We also analyzed the costs and benefits of declaring the area disease‐free prior to reintroduction and establishment of a healthy insurance population. After the monitoring session in May–June 2015, the probability that all devils had been successfully removed was close to 1, even when we accounted for a possible introduction of a devil to the site. Given this high probability and the baseline cost of declaring population absence prematurely, we found it was not cost‐effective to carry out any additional monitoring before introducing the insurance population. Considering these results within the broader context of Tasmanian devil management, managers ultimately decided to implement an additional monitoring session before the introduction. This was a conservative decision that accounted for uncertainty in model estimates and for the broader nonmonetary costs of mistakenly declaring the area disease‐free.

Handling overheads: optimal multi-method invasive species control - Christopher M. Baker; Paul R. Armsworth; Suzanne M. Lenhart (Theoretical Ecology, 2017)

Modelling tropical fire ant (Solenopsis geminata) dynamics and detection to inform an eradication project - Christopher M. Baker; Jarrod C. Hodgson; Elena Tartaglia; Rohan H. Clarke (Biological Invasions, 2017)

3D Cosmic Ray Muon Tomography from an Underground Tunnel - Elena Guardincerri; Charlotte Rowe; Emily Schultz-Fellenz; Mousumi Roy; Nicolas George; Christopher Morris; Jeffrey Bacon; Matthew Durham; Deborah Morley; Kenie Plaud-Ramos; Daniel Poulson; Diane Baker; et al. (Pure and Applied Geophysics, 2017)

Ensemble ecosystem modeling for predicting ecosystem response to predator reintroduction - Christopher M. Baker; Ascelin Gordon; Michael Bode (Conservation Biology, 2017)
Introducing a new or extirpated species to an ecosystem is risky, and managers need quantitative methods that can predict the consequences for the recipient ecosystem. Proponents of keystone predator reintroductions commonly argue that the presence of the predator will restore ecosystem function, but this has not always been the case, and mathematical modeling has an important role to play in predicting how reintroductions will likely play out. We devised an ensemble modeling method that integrates species interaction networks and dynamic community simulations and used it to describe the range of plausible consequences of 2 keystone‐predator reintroductions: wolves (Canis lupus) to Yellowstone National Park and dingoes (Canis dingo) to a national park in Australia. Although previous methods for predicting ecosystem responses to such interventions focused on predicting changes around a given equilibrium, we used Lotka–Volterra equations to predict changing abundances through time. We applied our method to interaction networks for wolves in Yellowstone National Park and for dingoes in Australia. Our model replicated the observed dynamics in Yellowstone National Park and produced a larger range of potential outcomes for the dingo network. However, we also found that changes in small vertebrates or invertebrates gave a good indication about the potential future state of the system. Our method allowed us to predict when the systems were far from equilibrium. Our results showed that the method can also be used to predict which species may increase or decrease following a reintroduction and can identify species that are important to monitor (i.e., species whose changes in abundance give extra insight into broad changes in the system). Ensemble ecosystem modeling can also be applied to assess the ecosystem‐wide implications of other types of interventions including assisted migration, biocontrol, and invasive species eradication.

Heat Survival and Phenotype Microarray Profiling of Salmonella Typhimurium Mutants - Turki M. Dawoud; Anita Khatiwara; Si Hong Park; Morgan L. Davis; Christopher A. Baker; Steven C. Ricke; Young Min Kwon (Current Microbiology, 2017)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Beta estimates of shares on the JSE Top 40 in the context of reference-day risk - Christopher Baker; Kanshukan Rajaratnam; Emlyn James Flint (Environment Systems and Decisions, 2016)

Using exposure windows to explore an elusive biomarker: blood manganese - Marissa G. Baker; Bert Stover; Christopher D. Simpson; Lianne Sheppard; Noah S. Seixas (International Archives of Occupational and Environmental Health, 2016)

Cross-polarized GPR imaging of fracture flow channeling - Georgios P. Tsoflias; Christopher Perll; Matthew Baker; Matthew W. Becker (Journal of Earth Science, 2015)

Decomposition of tree leaf litter on pavement: implications for urban water quality - Sarah E. Hobbie; Lawrence A. Baker; Christopher Buyarski; Daniel Nidzgorski; Jacques C. Finlay (Urban Ecosystems, 2014)

Sustainable Urban Systems - Christopher Kennedy; Lawrence Baker; Shobhakar Dhakal; Anu Ramaswami (Journal of Industrial Ecology, 2012)

Terrestrial biosphere model performance for inter‐annual variability of land‐atmosphere CO 2 exchange - T.F. Keenan; Ian Baker; Alan Barr; Philippe Ciais; Ken Davis; Michael Dietze; Danillo Dragoni; Christopher M Gough; Robert Grant; David Hollinger; Koen Hufkens; Ben Poulter; et al. (Global Change Biology, 2012)
Interannual variability in biosphere‐atmosphere exchange of CO 2 is driven by a diverse range of biotic and abiotic factors. Replicating this variability thus represents the ‘acid test’ for terrestrial biosphere models. Although such models are commonly used to project responses to both normal and anomalous variability in climate, they are rarely tested explicitly against inter‐annual variability in observations. Herein, using standardized data from the N orth A merican Carbon Program, we assess the performance of 16 terrestrial biosphere models and 3 remote sensing products against long‐term measurements of biosphere‐atmosphere CO 2 exchange made with eddy‐covariance flux towers at 11 forested sites in N orth A merica. Instead of focusing on model‐data agreement we take a systematic, variability‐oriented approach and show that although the models tend to reproduce the mean magnitude of the observed annual flux variability, they fail to reproduce the timing. Large biases in modeled annual means are evident for all models. Observed interannual variability is found to commonly be on the order of magnitude of the mean fluxes. None of the models consistently reproduce observed interannual variability within measurement uncertainty. Underrepresentation of variability in spring phenology, soil thaw and snowpack melting, and difficulties in reproducing the lagged response to extreme climatic events are identified as systematic errors, common to all models included in this study.

The pharmacological effects of the thermostabilising (m23) mutations and intra and extracellular (β36) deletions essential for crystallisation of the turkey β-adrenoceptor - Jillian G. Baker; Richard G. W. Proudman; Christopher G. Tate (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Climate vulnerability of ecosystems and landscapes on Alaska’s North Slope - Timothy G. F. Kittel; Barry B. Baker; Jonathan V. Higgins; J. Christopher Haney (Regional Environmental Change, 2011)

Hydrologic control of nitrogen removal, storage, and export in a mountain stream - Robert Jr. O. Hall; Michelle A. Baker; Christopher D. Arp; Benjamin J. Koch (Limnology and Oceanography, 2009)
Nutrient cycling and export in streams and rivers should vary with flow regime, yet most studies of stream nutrient transformation do not include hydrologic variability. We used a stable isotope tracer of nitrogen ( 15 N) to measure nitrate (NO 3 − ) uptake, storage, and export in a mountain stream, Spring Creek, Idaho, U.S.A. We conducted two tracer tests of 2‐week duration during snowmelt and baseflow. Dissolved and particulate forms of 15 N were monitored over three seasons to test the hypothesis that stream N cycling would be dominated by export during floods, and storage during low flow. Floods exported more N than during baseflow conditions; however, snowmelt floods had higher than expected demand for NO 3 − because of hyporheic exchange. residence times of benthic N during both tracer tests were longer than 100 d for ephemeral pools such as benthic algae and wood biofilms. Residence times were much longer in fine detritus, insects, and the particulate N from the hyporheic zone, showing that assimilation and hydrologic storage can be important mechanisms for retaining particulate N. Of the tracer N stored in the stream, the primary form of export was via seston during periods of high flows, produced by summer rainstorms or spring snowmelt the following year. Spring Creek is not necessarily a conduit for nutrients during high flow; hydrologic exchange between the stream and its valley represents an important storage mechanism.

CK2 and temperature compensation in Neurospora - Arun MEHRA; Mi SHI; Christopher L BAKER; Hildur V COLOT; Jennifer J LOROS; Jay C DUNLAP (Sleep and Biological Rhythms, 2009)

Late Quaternary speleothem pollen in the British Isles - Christopher J. Caseldine; Siobhán F. McGarry; Andy Baker; Chris Hawkesworth; Peter L. Smart (Journal of Quaternary Science, 2008)
As with many terrestrial areas, the British Quaternary sequence is characterised by incomplete, fragmentary records, whose correlation is based on stratigraphic or biostratigraphic techniques due to the lack of radiometric ages beyond the ∼40 kyr limit of 14 C dating. Speleothems (secondary cave calcite deposits) offer a significant advantage over many sources of palaeoenvironmental information; they can be dated to a high precision and accuracy by uranium‐thorium ( 238 U‐ 230 Th) thermal ionisation and inductively coupled plasma (ICP) mass spectrometry in the time period back to 500 kyr. They may also contain sufficient well‐preserved pollen representative of contemporary vegetation above the cave to allow palaeoenvironmental reconstruction. This study adopts the novel approach of combining pollen and thermal ionisation mass spectrometric (TIMS) U‐Th dating of British speleothems to produce well‐constrained palaeoenvironmental records. We report for the first time precisely dated records of pollen assemblages from speleothems suggesting the presence of thermophilous arboreal species in phases previously considered to have been consistently cool or cold and devoid of trees. Copyright © 2007 John Wiley & Sons, Ltd.

Discontinuities in stream nutrient uptake below lakes in mountain drainage networks - Christopher D. Arp; Michelle A. Baker (Limnology and Oceanography, 2007)
In many watersheds, lakes and streams are hydrologically linked in spatial patterns that influence material transport and retention. We hypothesized that lakes affect stream nutrient cycling via modifications to stream hydrogeomorphology, source‐waters, and biological communities. We tested this hypothesis in a lake district of the Sawtooth Mountains, Idaho. Uptake of NO 3 − and PO 4 −3 was compared among 25 reaches representing the following landscape positions: lake inlets and outlets, reaches >1‐km downstream from lakes, and reference reaches with no nearby lakes. We quantified landscape‐scale hydrographic and reach‐scale hydrogeomorphic, source‐water, and biological variables to characterize these landscape positions and analyze relationships to nutrient uptake. Nitrate uptake was undetectable at most lake outlets, whereas PO 4 −3 uptake was higher at outlets as compared to reference and lake inlet reaches. Patterns in nutrient demand farther downstream were similar to lake outlets with a gradual shift toward reference‐reach functionality. Nitrate uptake was most correlated to sediment mobility and channel morphology, whereas PO 4 −3 uptake was most correlated to source‐water characteristics. The best integrated predictor of these patterns in nutrient demand was % contributing area (the proportion of watershed area not routing through a lake). We estimate that NO 3 − and PO 4 −3 demand returned to 50% of pre‐lake conditions within 1‐4‐km downstream of a small headwater lake and resetting of nutrient demand was slower downstream of a larger lake set lower in a watershed. Full resetting of these nutrient cycling processes was not reached within 20‐km downstream, indicating that lakes can alter stream ecosystem functioning at large spatial scales throughout mountain watersheds.

Molecular provenance analysis for shy and white-capped albatrosses killed by fisheries interactions in Australia, New Zealand, and South Africa - Cathryn L. Abbott; Michael C. Double; Rosemary Gales; G. Barry Baker; Anna Lashko; Christopher J. R. Robertson; Peter G. Ryan (Conservation Genetics, 2006)

Past and present patterns of connectivity among populations of four cryptic species of freshwater mussels Velesunio spp. (Hyriidae) in central Australia - JANE HUGHES; ANDREW M. BAKER; CHRISTOPHER BARTLETT; STUART BUNN; KATRINA GOUDKAMP; JEMMA SOMERVILLE (Molecular Ecology, 2004)
We examined genetic structure and levels of connectivity among subpopulations within each of four cryptic species belonging to the freshwater mussel genus Velesunio . We used allozymes and a fragment of the mitochondrial cytochrome c oxidase I gene to examine genetic variation in populations from isolated waterholes, belonging to four major inland drainages in eastern Australia. Based on evidence from other invertebrates in the region we predicted that, in each species, we would find evidence of historical connectivity among populations from different drainages. This was clearly not the case, as for the two species that occurred in more than one drainage there was evidence of both current and past restriction to gene flow. Moreover, given the potential for extensive dispersal of these mussels through the river systems during flood times via their fish hosts, we predicted low levels of genetic variation among populations from waterholes in the same drainage. Contrary to our expectations, all four species showed some evidence of restricted gene flow among waterholes within drainages. This suggests that either (a) mussel larvae are not produced during flood times, when their fish hosts would be free to move between waterholes, or (b) mussel larvae are attached to their hosts at these times, but the fish movement is limited between waterholes.

Early induction of interferon-responsive mRNAs in Creutzfeldt-Jakob disease - Christopher A Baker; Zhi Yun Lu; Laura Manuelidis (Journal of NeuroVirology, 2004)

Predicting the Spread of Herbicide Resistance in Australian Canola Fields - Jeanine Baker; Christopher Preston (Transgenic Research, 2003)

A multi-component reaction (MCR) approach to the synthesis of highly diverse polymers with polypeptide-like features - Claude V. Robotham; Christopher Baker; Brian Cuevas; Khalil Abboud; Dennis L. Wright (Molecular Diversity, 2003)

Organization of Carboxysome Genes in the Thiobacilli - Gordon C. Cannon; Stefanie H. Baker; Ferda Soyer; Diana R. Johnson; Christopher E. Bradburne; Jennifer L. Mehlman; Paige S. Davies; Qin Li Jiang; Sabine Heinhorst; Jessup M. Shively (Current Microbiology, 2003)

Stalagmite lamina doublets: a 1000 year proxy record of severe winters in northwest Scotland? - Andy Baker; Christopher J. Proctor; William L. Barnes (International Journal of Climatology, 2002)
Stalagmites can contain annual luminescence laminae, and some samples provide long continuous chronologies from which climatic information can be extracted. One such site is Uamh an Tartair in Assynt, northwest Scotland, where most stalagmites contain continuous laminae sets for the last two to three millennia. At this site, the normal mode of deposition is for one luminescent lamina to be deposited in autumn, derived from luminescent organic matter that is flushed onto the sample from the overlying peat. However, in the stalagmite investigated here, 43 lamina doublets occur, where two laminae appear to be preserved in a winter. We argue, both from the timing of these events within the ‘Little Ice Age’, as well as from analogous situations in alpine streams, that the doublets occur due to the presence of a second, spring melt flush of organic matter. The interpretation of stalagmite double laminae, therefore, has considerable potential as a palaeoclimate proxy, and at our study site, we suggest one of severe winters over the last millennium. Copyright © 2002 Royal Meteorological Society.

Factors Influencing Succession: Lessons from Large, Infrequent Natural Disturbances - Monica G. Turner; William L. Baker; Christopher J. Peterson; Robert K. Peet (Ecosystems, 1998)

A Cromerian Complex stalagmite from the Mendip Hills, England - Andy Baker; Christopher J. Caseldine; Jackie Hatton; Christopher J. Hawkesworth; Alfred G. Latham (Journal of Quaternary Science, 1997)